Trans lives in a globalizing world
1 online resource (xi, 225 pages)
Keywords: "This volume seeks to explore contemporary trans lives in a world that is both global and increasingly globalizing, examining the nuances of the rights, identities, and politics that make up the varied spectrum of what has come to be included under the largely Western imposed label of "trans". Trans identities and rights have become increasingly prominent in the social imagination in recent years, and in a growing number of locales have also become hot button political issues. As trans individuals are demanding, and gaining, their rights, these debates are bringing issues of trans lives to the forefront of politics and into social discussions in nearly every country in the world today. In a series of essays covering the key themes of Identities, Rights, and Politics, this interdisciplinary collection presents an international range of topics spanning human rights and asylum seekers, to the Hijras of South Asia, and gender-affirming surgeries, all placing trans lives in a global(ized) context. This is an important contribution from a diverse group of established and emerging scholars seeking to position trans and transgender research in a global framework. It will be of key interest to researchers in Trans Studies, Gender Studies, Sexuality Studies, Cultural and Media Studies, Sociology, Politics, and Anthropology and for introductory courses in gender and LGBT issues"--